2015
DOI: 10.1097/sap.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Albumin Alone is Not a Predictor of 30-Day Outcomes in Pressure Ulcer Patients

Abstract: It is generally understood that hypoalbuminemic patients have elevated risks for surgical procedures. In pressure ulcer patients, it appears that these risks are not due to hypoalbuminemia alone, but rather a long list of attendant comorbidities. Consequently, hypoalbuminemia alone should not be used to determine the timing of a procedure for pressure ulcer surgery. Knowledge of these risks is necessary for patient counseling and surgical planning in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
0
11
2
Order By: Relevance
“…Low albumin has been noted as an indicator of a patient’s overall medical fitness, in the context of malnutrition. Contrary to a previous study that found low albumin not being associated with worse 30-day outcomes in pressure ulcer management [ 13 ], our findings show it as a risk factor for overall complications and specifically, wound dehiscence. This difference in findings may be related to the nonspecific nature of the marker, our patient cohort consisting of only flap reconstruction, or variability in methodology.…”
Section: Discussioncontrasting
confidence: 99%
“…Low albumin has been noted as an indicator of a patient’s overall medical fitness, in the context of malnutrition. Contrary to a previous study that found low albumin not being associated with worse 30-day outcomes in pressure ulcer management [ 13 ], our findings show it as a risk factor for overall complications and specifically, wound dehiscence. This difference in findings may be related to the nonspecific nature of the marker, our patient cohort consisting of only flap reconstruction, or variability in methodology.…”
Section: Discussioncontrasting
confidence: 99%
“…34 Also, patients with low preoperative albumin were almost twice as likely to have wound complications after laryngectomy, although the relationship between hypoalbuminemia and AEs is debated. 17 On regression analysis, weight loss was ratelinked to medical complications in our study, but not to surgical complications (data not shown). It is possible that malnourished patients are triaged to more aggressive reconstructive techniques (e.g., pedicled and free flaps), thus compensating for their baseline poor physiologic reserve.…”
Section: Discussionmentioning
confidence: 52%
“…Dyspnea may serve as a gross marker for overall poor health, presenting as a single common finding among a constellation of medical comorbidities in patients with overall poor health. [15][16][17] NSQIP defines dyspnea as "The patient describes difficult, painful, or labored breathing. "…”
Section: Discussionmentioning
confidence: 99%
“…After applying the full inclusion and exclusion criteria, a consensus was made for the discrepancies and 106 studies were eligible for analysis. 2,8,12 …”
Section: Resultsmentioning
confidence: 99%